Pelatihan Manajemen Dasar Dalam Usaha Pada KSP Sahabat Mitra Sejati - Amrullah, Amrullah; Indrawan , Dedek; Febriana, Elza Tia (Universitas Dehasen Bengkulu, 2021)
Basic business management training at KSP Sahabat Mitra Sejati aims to improve members' skills and knowledge in managing their businesses. This study evaluates the impact and effectiveness of the training program in improving the performance and sustainability of micro enterprises in the financial institution. The research methods used include surveys, interviews, and data analysis to measure changes before and after the training. The results showed a significant improvement in members' knowledge and management skills after the training. Trainees also reported improvements in the operational efficiency and financial management of their businesses. The active involvement of members in the training process was also a key factor in the success of the program. In conclusion, the basic business management training at KSP Sahabat Mitra Sejati had a positive impact in improving members' business skills and performance. The program not only provides individual benefits, but also strengthens social cohesion and economic growth in the community. Further efforts are needed to develop and expand this training program to support the growth and sustainability of microenterprises at the local level.